ASPEK HUKUM SURROGATE MOTHER DALAM PERSPEKTIF HUKUM INDONESIA - Judiasih, Sonny Dewi; Dajaan, Susilowati Suparto (Fakultas Hukum Universitas Padjadjaran, 2017)
AbstrakSurrogate Mother, ibu yang menyewakan rahimnya, adalah seorang wanita yang mengandung anak yang benihnya berasal dari pasangan lain dan setelah wanita tersebut melahirkan, maka wanita tersebut akan memberikan anak tersebut kepada pasangan darimana benih tersebut berasal. Artikel ini menguraikan kedudukan surrogacy agreement menurut Hukum perjanjian di Indonesia dan status hukum anak yang lahir dari surrogate mother, pengaturan pelaksanaan surrogate mother di beberapa negara sebagai perbandingan dan untuk memahami dan mengkaji perlunya pengaturan surrogate mother di Indonesia. Metode pendekatan yang digunakan adalah yuridis normatif dan data diperoleh melalui studi kepustakaan dan studi lapangan yang dianalisis secara normatif kualitatif. Hasil penelitian bahwa Indonesia belum memiliki aturan yang spesifik mengenai surrogate mother, dalam pelaksanaan surrogate mother yang terkait dengan surrogacy agreement tidak dimungkinkan dilakukan di wilayah hukum Indonesia, status anak yang lahir dari surrogate mother dalam kaitan dengan pengaturan Undang-undang No. 1 Tahun 1974 tentang Perkawinan, bahwa anak tersebut merupakan anak sah dari surrogate mother, bukan anak dari orang tua yang menitipkan benih di rahim surrogate mother. Banyaknya praktik yang dilakukan oleh masyarakat terkait dengan surrogate mother, maka perlu dibuat aturan sebagai panduan dalam pelaksanaan surrogate mother yang dimaksudkan untuk ketertiban dan kepastian hukum. Kata Kunci: aspek hukum, surrogate mother, surrogacy. AbstractSurrogate mother is defined as woman carrying another person’s embryo and gives birth to a baby for the person who donors the embryo. The unique characteristic arises from who will be called as the parent. Surrogate mother exists because the wife usually obtain something wrong in her uterus thus cannot carrying a child, subsequently the role of the wife to carry and give birth is transferred to another woman, either voluntarily or because of the money. The purpose of this research is to comprehend and analyse the status of surrogacy agreement in Indonesian contract law; the status of child born through surrogacy; the regulations regarding surrogate mother implemented in several countries as comparison; lastly, to formulate a suitable regulation of surrogate mother in Indonesia. The method used by the author in discussing problems in this research is normative. Specifications research used is by analyzing juridical analysis or the problem based on the statutory provisions related to family law and contract law, literature, other sources related to this research. To obtain the necessary data through the study of literature and field studies were obtained for onward normative data is analyzed normative qualitatively. The results of the research are, Indonesia do not have specific regulationns regarding surrogate mother,thus surrogacy can not be implemented in Indonesia. In relation with Law Number 1 of 1974 concerning marriage, the status of child born through surrogacy is the legitimate child of the surrogate mother, not the intended parent. As a result of comparison with several countries, many countries reject and many accept the existence of surrogate mother. Lastly, due to rampant practice of surrogacy in the society, the writer concludes the government need to promptly draft a regulation as a guidance of surrogacy practice to maintain order and legal certainty in the society.Keywords: gestational surrogacy, legal status, surrogate mother, traditional surrogacy. DOI : https://doi.org/10.23920/jbmh.v1n2.14